Daratumumab-based immunotherapy vs. lenalidomide, bortezomib and dexamethasone in transplant-ineligible newly diagnosed multiple myeloma: a systemic review - Tang, Wenjiao; Zhang, Li; Zheng, Yuhuan; Pan, Ling; Niu, Ting (Frontiers in Oncology, 2024)
Background: Since no randomized controlled trials have directly compared the efficacy and safety of immunotherapy with daratumumab versus lenalidomide/bortezomib/dexamethasone (RVD) in the frontline treatment of transplant-ineligible newly diagnosed multiple myeloma (TIE-NDMM), this study systematically reviewed the clinical studies regarding immunotherapy with daratumumab and RVD regimen in the treatment of TIE-NDMM to explore the optimization direction of the best firstline therapy.Methods: The Cochrane Library, PubMed, Embase, and Web of Science databases were searched to collect studies on regimens containing daratumumab or RVD/RVD-lite for TIE-NDMM. Pooled and meta-analysis was then performed to compare the overall response rate (ORR), stringent complete remission (sCR) and CR rate, progression-free survival (PFS), overall survival (OS) and treatmentrelated discontinuation rate between daratumumab-containing immunotherapy regimen and RVD/RVD-lite regimen by using R 4.3.1 software.Results: Nine prospective clinical trials were included, including 1795 TIE-NDMM or NDMM without intent for immediate ASCT. Among them, 938 patients were treated with daratumumabbased immunotherapy and 857 with RVD/RVD-lite regimens. Meta-analysis results showed that The daratumumab-based regimen showed a significantly higher CR/sCR rate than RVD/RVD-lite for TIE-NDMM (47% vs. 24%, P<0.01). The median PFS of the daratumumab-based and RVD/RVDlite groups were 52.6 months and 35.1 months respectively (HR 0.77, 95%CI, 0.66-0.90). The median OS of both groups was not reached, and there were no significant differences in OS between the two groups (HR 1.03, 95%CI,. The therapy discontinuation rate led by adverse events was significantly higher in the RVD/RVD-lite group than in the daratumumab-based regimen group for the TIE-NDMM (16% vs. 7%, P=0.03).Conclusions: This meta-analysis suggests that daratumumab-containing immunotherapy is superior to RVD in the depth of treatment efficacy, progression-free survival, and lower treatment-related discontinuation rates. Limited by the lack of head-to-head clinical trials, this conclusion needs to be verified by concurrent cohort studies.